Evolution of the Lower Palaeozoic Nanhua Foreland Basin and nature of the Wuyi-Yunkai Orogeny, South China - Yao, Weihua (Curtin University, 2014)
This thesis reports results of a combined sedimentological, stratigraphic, detrital provenance, geochronological, isotopic and geochemical study of the early Palaeozoic South China Block (SCB). It reveals the driving mechanism for the Wuyi–Yunkai orogeny, and the sedimentary and provenance evolution of the lower Palaeozoic Nanhua foreland basin. The thesis further explores possible tectonic interactions between the SCB and northern India during the assembly of Gondwanaland in late Neoproterozoic to early Palaeozoic time.